On the traces of w2,p() for a lipschitz domain - G. Duran, Ricardo; Muschietti, Maria Amelia (Revista Matemática Complutense, 2001)
We extend to the case 1 < p the results obtained by Geymonat and Krasucki for p = 2 on the characterization of the traces of W2,p() for a bounded Lipschitz domain.